2004
DOI: 10.1002/art.20077
|View full text |Cite
|
Sign up to set email alerts
|

Prevalences of polyarteritis nodosa, microscopic polyangiitis, Wegener's granulomatosis, and Churg‐Strauss syndrome in a French urban multiethnic population in 2000: A capture–recapture estimate

Abstract: Objective. To estimate the prevalences of polyarteritis nodosa (PAN), microscopic polyangiitis (MPA), Wegener's granulomatosis (WG), and Churg-Strauss syndrome (CSS).Methods. Cases were collected in Seine-St. Denis County, a northeastern suburb of Paris, which has 1,093,515 adults (>15 years), 28% of whom are of non-European ancestry. The study period encompassed the entire calendar year 2000. Cases were identified by general practitioners, the departments of all the public hospitals and 2 large private clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
235
5
19

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 490 publications
(267 citation statements)
references
References 29 publications
8
235
5
19
Order By: Relevance
“…66.1711.4 years) and 77 unrelated healthy Japanese controls (46 men, 31 women, 25.975.6 years). Incidence of MPA in males and females appears to be approximately similar in Caucasians; 11,12 however, a nationwide study in Japan reported a female preponderance ANCA-associated vasculitis (male : female 1 : 1.8), among which MPA was most prevalent. 13 Diagnosis of MPA was based on the Japanese criteria.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…66.1711.4 years) and 77 unrelated healthy Japanese controls (46 men, 31 women, 25.975.6 years). Incidence of MPA in males and females appears to be approximately similar in Caucasians; 11,12 however, a nationwide study in Japan reported a female preponderance ANCA-associated vasculitis (male : female 1 : 1.8), among which MPA was most prevalent. 13 Diagnosis of MPA was based on the Japanese criteria.…”
Section: Resultsmentioning
confidence: 96%
“…11 Since HLA-DRB1*0901 is a common allele in Asian populations but rare in other populations, it was suggested that such a difference in the genetic background may be related to apparently higher prevalence of MPA in Japan as compared with Wegener's granulomatosis, which is more frequent in Caucasian populations. 2 Owing to the extensive linkage disequilibrium (LD) in the HLA region, statistical association with HLA-DRB1*0901 does not necessarily mean that HLA-DRB1*0901 molecule is involved in the pathogenesis of MPA.…”
Section: Introductionmentioning
confidence: 99%
“…The sex man/woman ratio is of 1.38. At diagnosis 50% of the patients live in the Côte d'Or department, 37.5% in the Saône-et-Loire, 8.5% in Nièvre and 4% in Yonne (p=0.02). In 48 % the patients live in rural zone in and in 52% in urban zone (p=NS).…”
Section: Resultsmentioning
confidence: 99%
“…Some minor forms have probably been followed only in a consultation or in outpatient clinic and are not recorded here. However, CSS is a rare pathology, multisystemic, seldom taken care of exclusively in outpatient [8]. These results are also superimposable with other important European series (incidence: 1-4/million inhabitants/ annum within the general population [9][10][11][12] and prevalence: 2-13/million inhabitants [12][13][14]), confirming the absence of North-South or East-West gradient within this pathology [13] or evolution in time [11] contrary to other vasculitis as the disease of Wegener whose incidence is currently in increase and who has a North-South decreasing gradient [15].…”
Section: Discussionmentioning
confidence: 99%
“…The absence of hepatitis B, which is known to be strongly related with PAN, does not exclude the diagnosis. It was estimated that hepatitis B is causative for 30% and more recently -for 7-10% of PAN cases [6,7]. Given that, he met ACR criteria for PAN even before the kidney pathology became available.…”
Section: Discussionmentioning
confidence: 99%